The Evolution of Labor Market Disparities between Hispanic and Non-hispanic Men: 1970-2019 - Ioannis Kospentaris; Leslie S. Stratton (Institute of Labor Economics (IZA), 2023)
We describe how ethnic disparities in the labor market between prime aged Hispanic and non-Hispanic white men have evolved over the last 50 years. Using data from the March CPS, the Census, and the ACS, we examine several employment and earning outcomes. Hispanics have experienced sizable gains to employment: from a negative 2% prior to 1990 to a positive 4% after 2010 compared to non-Hispanics. In terms of earnings, Hispanics face a substantial negative disparity between 20% and 30% with some improvement after 2000. Most of the employment gain is driven by those with less than a high school degree, while the earnings disparity increases with education. Comparing Hispanic immigrants with natives reveals much of the employment and earnings gains are attributable to Hispanic immigrants, particularly immigrants not fluent in English.
Keywords: J15; J21; J31; J71; 330; Hispanics; ethnicity; disparities; earnings; employment; education; immigration